Malignant Hypertension: Clinical Manifestations of 7 Cases - Steinegger, K.; Bergin, C.; Guex-Crosier, Y. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: Malignant hypertension is defined by marked systemic arterial hypertension with retinal haemorrhages, exudation or papilloedema. Due to the rarity of this disease and due to its non-specific symptoms and lesions, the diagnosis can be challenging. Patients and Methods We investigated the types of symptoms and ocular lesions observed with ocular fundus examination, ocular fundus photography, fluorescein angiography and optical coherence tomography in a small case series of 7 patients with malignant hypertension. Results: Median systolic blood pressure (BP) was 205 mmHg ± 21. Median diastolic BP was 150 mmHg ± 16. Decrease in visual acuity (6/7 patients) and scotoma (5/7) were the main symptoms and Elschnig spot, flamed shaped haemorrhage, serous retinal detachment, cotton wool spots and optic nerve oedema were the five most frequently observed lesions. A regression of lesions was observed after therapy of systemic hypertension. Conclusion: The association of multiple lesions strongly suggests malignant hypertension. However even in cases with only one lesion malignant hypertension should be kept in mind.
Keywords: Bluthochdruck; maligne Hypertonie; Elschnig-Fleck; exsudative Netzhautablösung